Population and attacks of Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) on corn inoculated with endophytic entomopathogenic fungi from South Sumatra, Indonesia - Rindiani, Dellania Eka; Herlinda, Siti; Suwandi, Suwandi (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2024)
Spodoptera frugiperda damage in South Sumatra reached 100%. Biological control of S. frugiperda using entomopathogenic fungi has been widely practiced. This study aimed to determine S. frugiperda larval abundance and infestation in maize inoculated with endophytic entomopathogenic fungi. The three fungal isolates used in the current study consisted of one species of Beauveria bassiana (isolate code: JgSPK), one species of Penicillium citrinum (isolate code: JaTpOi (2)) and one species of Metarhizium anisopliae (isolate code: CaTpPga). Egg and larval, incidence and severity of S. frugiferda infestation were observed. All endophytic entomopathogenic fungal isolates could siginifcantly decrease the incidence and severity caused by S. frugiperda larvae. Corn seeds treated with endophytic entomopathogenic fungi did not affect the population of eggs and larvae. Fluctuations of the egg and larval population tended to be influenced by corn age.